Suitability of testers to characterize provitamin a content and agronomic performance of tropical maize inbred lines - Maazou, Abdoul-Raouf Sayadi; Adetimirin, Victor O.; Gedil, Melaku; Meseka, Silvestro; Mengesha, Wende; Menkir, Abebe (Frontiers in Genetics, 2022)
Vitamin A Deficiency poses health risks for children, pregnant women and nursing mothers in sub-Saharan Africa (SSA) and Southeast Asia. Provitamin A-biofortified maize varieties can contribute to minimizing the adverse effects of vitamin A deficiency in areas where maize is a staple food crop. Identifying suitable testers is important to breed provitamin A-biofortified hybrid maize. This study was therefore conducted to (i) assess the suitability of maize inbred lines with contrasting levels of provitamin A (one with high and one with low provitamin A concentration) to assess the combining ability of maize inbred lines in accumulating provitamin A and other carotenoids, and grain yield (ii) confirm the mode of inheritance of provitamin A and grain yield, and (iii) identify promising inbred lines with desirable combining ability effects for use to develop high yielding provitamin A-biofortified hybrids. The inbreds crossed to the two inbred testers were evaluated in four environments for carotenoid content and eight environments for agronomic performance. The combined analysis of variance revealed a significant genetic variation among the testcrosses for all carotenoids, grain yield and other agronomic traits. The mode of inheritance for grain yield, other agronomic traits, provitamin A and other carotenoids was regulated by both additive and non-additive gene effects with a prominence of additive gene effects. The high provitamin A tester that displayed positive GCA effects for β-Carotene and provitamin A content, broader agronomic performance of testcrosses, and higher levels of provitamin A in testcrosses can be considered suitable for breeding programs developing provitamin A-biofortified hybrids. The inbred lines TZI2012, TZI2142, TZI2130, TZI2065-2, TZI2161, TZI2025, TZI1278, TZI1314, TZI1304, and TZI2032 with positive GCA effects for grain yield and provitamin A content could be used as parental lines to develop source population of new inbred lines and high-yielding hybrids with elevated levels of provitamin A. The best performing hybrids are promising for release as high yielding provitamin A maize hybrids after further evaluations.